2023
DOI: 10.3389/fsurg.2022.1086960
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SARS-CoV-2 measures on patient samples and complication rates in spine surgery – A single center analysis

Abstract: ObjectiveOver the past two years during the pandemic, the German health system has taken drastic measures, like the continuous use of face masks for all staff, restrictions of hospital visits as well as cancellation of elective surgical procedures. As a potential side effect of these measures, a significant reduction of surgical site infections was reported for neurosurgical patients. The purpose of our study was to analyze the impact of these measures on spinal surgery.MethodsWe performed a retrospective anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…An authoritative review from an international consensus group coherently summarized the current state-of-the-art in the field as it pertains to the pathogenesis of SARS-CoV-2-mediated immune-thrombotic complications after surgery Bunch et al The authors introduced the new entity of "COVID-associated coagulopathy" and explained the underlying hypothesis related to SARS-CoV-2-induced endothelitis as the root cause of an imbalance between fibrinolysis and fibrinolytic shutdown Bunch et al The clinical implications pertain to adjudicating the timing of elective surgical procedures in COVID-19 patients and to monitor the "rollercoaster" stages of COVID-associated coagulopathy by point-of-care-guided viscoelastic hemostatic assays, such as thromboelastography (Figure 1). The authors furthermore provided specific clinical recommendations for perioperative anticoagulation in COVID-19 patients for a variety of surgical subspecialties, including general surgery, cardiothoracic and (22). The authors attributed the lack of decreased surgical site infections, in spite of the COVID-19 preventative measures, to higher rates of emergency surgical spine procedures during the pandemic (22).…”
Section: Editorial On the Research Topic The Impact Of Covid-19 On Im...mentioning
confidence: 99%
See 3 more Smart Citations
“…An authoritative review from an international consensus group coherently summarized the current state-of-the-art in the field as it pertains to the pathogenesis of SARS-CoV-2-mediated immune-thrombotic complications after surgery Bunch et al The authors introduced the new entity of "COVID-associated coagulopathy" and explained the underlying hypothesis related to SARS-CoV-2-induced endothelitis as the root cause of an imbalance between fibrinolysis and fibrinolytic shutdown Bunch et al The clinical implications pertain to adjudicating the timing of elective surgical procedures in COVID-19 patients and to monitor the "rollercoaster" stages of COVID-associated coagulopathy by point-of-care-guided viscoelastic hemostatic assays, such as thromboelastography (Figure 1). The authors furthermore provided specific clinical recommendations for perioperative anticoagulation in COVID-19 patients for a variety of surgical subspecialties, including general surgery, cardiothoracic and (22). The authors attributed the lack of decreased surgical site infections, in spite of the COVID-19 preventative measures, to higher rates of emergency surgical spine procedures during the pandemic (22).…”
Section: Editorial On the Research Topic The Impact Of Covid-19 On Im...mentioning
confidence: 99%
“…The authors furthermore provided specific clinical recommendations for perioperative anticoagulation in COVID-19 patients for a variety of surgical subspecialties, including general surgery, cardiothoracic and (22). The authors attributed the lack of decreased surgical site infections, in spite of the COVID-19 preventative measures, to higher rates of emergency surgical spine procedures during the pandemic (22). The special edition concludes with a case report on three patients with COVID-19 who sustained severe osteomyelitis of the jaw as a rare but severe infectious complication Kvolik Pavic et al The authors hypothesized that the SARS-CoV-2-induced immune dysfunction and microvascular changes contributed to the increased vulnerability for severe infection in patients with COVID-19 Kvolik Pavic et al…”
Section: Editorial On the Research Topic The Impact Of Covid-19 On Im...mentioning
confidence: 99%
See 2 more Smart Citations
“…Reports from developed countries suggested that the pandemic conditioned a slight reduction in operative capacities, and affected mainly elective procedures [ 4 , 5 ]. Some centers reported an increase in the number of urgent procedures with stable complication rates, and no higher mortality rate than had been reported in the pre-pandemic period [ 6 , 7 ]. Developing countries with higher healthcare system stress reported a considerable impact by decreasing the number of scheduled surgeries, increasing the proportion of urgent surgeries, and increasing the proportion of emergency surgeries [ 8 , 9 ], while in other countries there was an increase in hospital mortality and in the cost of procedures [ 10 ].…”
Section: Introductionmentioning
confidence: 99%